(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The present study contributes to the subsisting literature on Word-of-Mouth by identifying the demographic and behavioural factors that motivate people towards making e-referrals of mobile banking applications. Also the influence of incentives and incentive amount is measured. The data for the study is collected from 120 respondents. The results suggest that education, age, satisfaction, trust, involvement, existing word-of-mouth, usefulness, credibility, incentive and incentive amount positively influence a customer’s choice of referring people electronically.